A disease, disorder, illness or condition: How to label epilepsy?. (14th March 2017) - Noble, A. J.; Robinson, A.; Marson, A. G.
Abstract : The International League Against Epilepsy (ILAE) is an important source of guidance for health professionals when it comes to epilepsy. Their latest recommendation that epilepsy should no longer be called a "disorder, " but a "disease" has though caused controversy. The ILAE contends the change will improve epilepsy's image. Some clinicians and other organizations fear the change may not though be accepted by patients as in common parlance "disease" can be associated with "contagiousness"/"infection." To allow practicing clinicians to make informed judgements about what language they use, we completed the first study to assess the preferences of those with epilepsy and significant others and explore if any of their characteristics were associated with preference. Via epilepsy interest groups and associations in England, Wales, Scotland and the Republic of Ireland, 971 patients and significant others were surveyed. Participants identified which of four labels for epilepsy ("disorder, " "illness, " "disease, " "condition") they favoured and rated each using a Likert‐scale. Patients' median age was 39; 69% had experienced seizures in the prior year. "Condition" was favoured by most patients (74.3%) and significant others (71.2%). Only 2.2% of patients and 1.2% of significant others chose "disease"; it received a median Likert‐rating indicating "strongly dislike." Multinomial logistic regression found it was not possible to reliably distinguish between participants favouring the different terms on the basis of demographics. The ILAE's position is at odds with what most patients and carers want and we discuss the implications of this.